PHYSIOTHERAPY STRATEGY FOR PATIENT WITH HERNIATED DISC - Nastiti, Rindang Rizky; Rahayu, Umi Budi (Academic Physiotherapy Conference Proceeding, 2021)
Introduction : Hernia Nucleus Pulposus (HNP) is a condition that occurs due to biochemical changes in the spinal disc tissue. This change will cause rupture of the annulus fibrosus which makes the nucleus pulposus bulging (protrudes) towards the spinal canal which will put pressure on the nerve roots, causing symptoms in the form of neurological pain. Case Presentation : Mrs. E is a 37-year-old housewife with low back pain due to disc herniation with a history of post chemotherapy for breast cancer. Pain is felt when the patient is undergoing treatment, pain is like being stabbed and radiates from the lower back to both legs and especially the right leg, numbness and weakness in the right leg Management and Outcome : Treatments provided such us infrered, TENS, stretching, and core stability exercise performed 2 times a week for 4 weeks. The measuring instrument used is NRS, MMT, and Oswestry Disability Index. Discussion : One type of exercise that can be done for patients with lumbar HNP is core stability exercises in the form of abdominal hollowing exercises, prone lying, prone on elbow, prone press-up, prone press up with overpressure which can be selected by taking into account the ability of the patient. Core stability exercise is an exercise that functions as a synergistic activation that contracts the trunk and pelvic stabilizer muscles, to improve the control of the neuromuscular system and the strength of the trunk muscles and to maintain spinal stability which functions to maintain body posture and optimize the patient to control the trunk position. Core stability performed by the patient is able to reduce pressure on the nucleus pulposus during the spine extension position, so that nerve clamping can be reduced and can reduce pain symptoms, Conclusion : It can be concluded that in this case, the provision of physiotherapy programs in the form of infrared, TENS, stretching hamstrings, and core exercises performed 2 times a week for 4 weeks was able to reduce pain and improve functional ability in patients.